2014
DOI: 10.1021/nn406127s
|View full text |Cite
|
Sign up to set email alerts
|

PbS Nanoparticles Capped with Tetrathiafulvalenetetracarboxylate: Utilizing Energy Level Alignment for Efficient Carrier Transport

Abstract: We fabricate a field-effect transistor by covalently functionalizing PbS nanoparticles with tetrathiafulvalenetetracarboxylate. Following experimental results from cyclic voltammetry and ambient-pressure X-ray photoelectron spectroscopy, we postulate a near-resonant alignment of the PbS 1Sh state and the organic HOMO, which is confirmed by atomistic calculations. Considering the large width of interparticle spacing, we observe an abnormally high field-effect hole mobility, which we attribute to the postulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 66 publications
1
57
0
Order By: Relevance
“…34 Since the optoelectronic properties of PbS NC ensembles bear many opportunities for applications in solar cells or photodetectors, a number of ligand exchange procedures with small organic or inorganic molecules as well as single atom passivation strategies have been developed, all of which greatly increase the carrier mobilities within the SL of NCs. 28,33,[35][36][37][38][39][40][41][42][43][44] Due to the short interparticle spacing imposed by these ligands, structural coherence is mostly lost in such superlattices, but in rare cases it has been demonstrated that significant long-range order and even mesocrystallinity can be preserved. 25,35,45 However, a persisting problem of these protocols is that they are prone to introduce defects in the superlattice structure with some degree of granularity and significantly smaller grain sizes, which poses difficulties in determining the angular correlation with a meaningful statistical distribution.…”
mentioning
confidence: 99%
“…34 Since the optoelectronic properties of PbS NC ensembles bear many opportunities for applications in solar cells or photodetectors, a number of ligand exchange procedures with small organic or inorganic molecules as well as single atom passivation strategies have been developed, all of which greatly increase the carrier mobilities within the SL of NCs. 28,33,[35][36][37][38][39][40][41][42][43][44] Due to the short interparticle spacing imposed by these ligands, structural coherence is mostly lost in such superlattices, but in rare cases it has been demonstrated that significant long-range order and even mesocrystallinity can be preserved. 25,35,45 However, a persisting problem of these protocols is that they are prone to introduce defects in the superlattice structure with some degree of granularity and significantly smaller grain sizes, which poses difficulties in determining the angular correlation with a meaningful statistical distribution.…”
mentioning
confidence: 99%
“…Similar works on mixtures of DTCP with P3HT or Au nanoparticles indicate that this conversion can indeed be achieved [5,26]. Since significantly coupled PbS QDs exhibit much higher carrier mobilities than P3HT, establishing a similar photoswitchability in this material is expected to give rise to optically addressable transistors or even memory elements with high efficiencies [27,28].…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, organic molecules (both ligands and additives) in CQD films can affect the electronic coupling between the adjacent dots. Tuning the (mis)alignment of the HOMO or LUMO of the molecule with the matching states in the CQDs allows for suppressing or enhancing the coupling for one of the carriers, and determining changes in the apparent device polarity . Addition of ligands can also modify the density of states of the single CQDs, as observed from the increased absorbance of CQDs capped with arene‐thiolates, and the effect can be fine‐tuned with functional side groups attached to the aromatic ring …”
Section: Surface‐based Control Of the Electronic Propertiesmentioning
confidence: 99%